Historical Development of Adjective Accentuation in Croatian (suffixless, *-ьnъ and *-ъkъ adjectives) - Kapović, Mate (Array, 2011)
The article deals with the historical development of the accentuation of suffixless (root), *-ьnъ and *- ъkъ adjectives. Their development is analyzed in detail from their Proto-Slavic origin to their modern reflexes in Štokavian, Čakavian and Kajkavian dialects